Efficacy of steroid therapy in the acute stage of anti-NMDAR and anti-MOG antibody overlapping encephalitis: a case report and literature review - Kondo, Hikari; Takeuchi, Yuko; Niwa, Junichi; Yoshida, Kenji; Takemura, Naoaki; Hosoyama, Sachiko; Kaga, Tomotsugu; Kaneko, Kimihiko; Mabuchi, Naoki (Frontiers in Immunology, 2024)
Background: Recently, cases of overlapping encephalitis caused by anti-N-methyl-D-aspartate receptor (anti-NMDAR) and anti-myelin oligodendrocyte glycoprotein (MOG) antibodies have been reported, and their clinical characteristics are gradually becoming clear. Acute-phase treatment typically involves the use of steroids, and although some studies have suggested that steroids can be effective, the extent of their efficacy has not yet been fully explored. Case Presentation: We present the case of a 25-year-old man with anti-NMDAR and anti-MOG antibody overlapping encephalitis who showed considerable improvement after steroid treatment. To gain a deeper understanding of the efficacy of steroids in managing this condition, we conducted a literature review of cases of anti-NMDAR and anti-MOG antibody double-positive encephalitis that were treated with steroids during the acute phase. Thirteen cases were analyzed, including a new case diagnosed at our hospital. All patients showed improvement after receiving steroid treatment in the acute phase. Ten patients did not have any sequelae, and nine of them showed a rapid or major response during the acute phase. In contrast, three patients experienced sequelae (mild cognitive decline, visual impairment, and memory impairment, respectively), with their response to steroids in the acute phase being slow or limited. Relapses occurred in five patients, in one patient during steroid tapering, and in another two patients after cessation of steroids. Conclusion: Steroid therapy can be effective in the acute stage of anti-NMDAR and anti-MOG antibody overlapping encephalitis. A positive prognosis may be expected in patients who experience substantial improvement with steroid therapy during the acute phase.